Spatial Dynamics of Land Use Changes and Land Carrying Capacity of Settlement in Palaran District Year 2014 – 2024 - Randi Arman Pratama; Ananto Aji; Juhadi Juhadi (Universitas Lambung Mangkurat, 2025)
This study examines spatial dynamics of land use change and the capacity of land to support residential development in Palaran Subdistrict, Samarinda City, over a ten-year period. The objectives are to map temporal shifts in land cover for 2014, 2019, and 2024; to evaluate land suitability for housing based on eight bio-physical parameters stipulated by national regulation; and to quantify the carrying capacity and population support capacity of suitable land. The methodology integrates multitemporal satellite imagery processing, supervised classification with a random decision forest algorithm, geographic information system overlay analysis, and field validation at two hundred sampling points. Results reveal a forty-one percent increase in built-up area and a seventy-percent decrease in agricultural land, with over eighty-seven percent of the study area classified as highly suitable for residential use. Calculations of land support capacity indicate a significant surplus relative to current population levels, underscoring opportunities for sustainable urban expansion and evidence-based spatial planning.